2012 IEEE Nuclear Science Symposium and Medical Imaging Conference Record (NSS/MIC) 2012
DOI: 10.1109/nssmic.2012.6551640
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for a partial-ring, multi-modal compatible whole-body TOF PET scanner: Flexible PET

Abstract: Along with the popularization and technological maturation of integrated PET-CT, the center of research interest has moved to integrated PET-MR. In this situation, we are developing a multi-modal compatible flexible PET scanner. In our concepts, the scanner consists of adjustable two detector units and their support apparatus, and then scans a patient lying on a bed equipped by other medical imaging/non-imaging device.Therefore, depending on the size and shape of the patient and the patient bed and other deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…As shown in Figure 1, the fxPET scanner is a partial-ring scanner rather than a conventional full-ring scanner, and its limited angular coverage results in missed line-of-responses in sinogram space. Degradation of image quality caused by data loss due to incomplete coincidence data was confirmed by a previous phantom study and was found to be reduced by using TOF information and more suitable list-mode reconstruction algorithms (8,9). Each crystal is 20 mm long, with a cross-sectional area of 2.9 • 2.9 mm and 4-layer depth-of-interaction capability.…”
Section: Description Of Fxpet Systemmentioning
confidence: 67%
See 2 more Smart Citations
“…As shown in Figure 1, the fxPET scanner is a partial-ring scanner rather than a conventional full-ring scanner, and its limited angular coverage results in missed line-of-responses in sinogram space. Degradation of image quality caused by data loss due to incomplete coincidence data was confirmed by a previous phantom study and was found to be reduced by using TOF information and more suitable list-mode reconstruction algorithms (8,9). Each crystal is 20 mm long, with a cross-sectional area of 2.9 • 2.9 mm and 4-layer depth-of-interaction capability.…”
Section: Description Of Fxpet Systemmentioning
confidence: 67%
“…The most likely cause of the lack of superior performance was degradation of image quality caused by incomplete coincidence data derived from the partial-ring detector. Two studies reported that accurate TOF information improved reconstruction image quality in a partial-ring PET scanner with no detector rotation (8,9). Therefore, the technology of TOF was added to the fxPET system to improve image quality, although the image quality of fxPET was not superior to that of commercial WB PET scanners that do not have TOF capability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system has two partial-ring (arc-shaped, 135°) detectors with depth-of-interaction (DOI) and time-of-flight (TOF) capability [2,5]. These detectors effectively compensate for the count loss caused by incomplete detector coverage [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, depending on the size and shape of the patient and the patient bed and other demands, the detector geometry can be changed flexibly. [14]. Chih-Chieh Liu et al proposed a crystal arrays with curved surfaces to reduce the dead space between detector modules and hence improve the sensitivity of PET.…”
Section: Introductionmentioning
confidence: 99%